Protecting-group-free glycosylation of phosphatidic acid in aqueous media. Issue 10 (16th February 2023) - Kano, Koki; Ishii, Nozomi; Miyagawa, Atsushi; Takeda, Hiroaki; Hirabayashi, Yoshio; Kamiguchi, Hiroyuki; Greimel, Peter; Matsuo, Ichiro
Abstract : Convenient one-pot synthesis of anomeric glycosyl phosphates by direct condensation of unprotected glucose with phospholipid derivatives in aqueous media while retaining high levels of stereoselective control. Abstract : The glycosylation of unprotected carbohydrates has emerged as an area of significant interest because it obviates the need for long reaction sequences involving protecting-group manipulations. Herein, we report the one-pot synthesis of anomeric glycosyl phosphates through the condensation of unprotected carbohydrates with phospholipid derivatives while retaining high stereo- and regioselective control. The anomeric center was activated using 2-chloro-1, 3-dimethylimidazolinium chloride to facilitate condensation with glycerol-3-phosphate derivatives in an aqueous solution. A water/propionitrile mixture provided superior stereoselectivity while maintaining good yields. Under these optimized conditions, the condensation of stable isotope-labeled glucose with phosphatidic acid provided efficient access to labeled glycophospholipids as an internal standard for mass spectrometry.